(untitled) - Cataldo, Corinne Balog (Belmont, Canada, 1998)
Organized by diets rather than organ systems or disease states, this text includes margin definitions, key points, self-check quizzes, self-studies, case studies and question-and-answer style "Nutrition in Practices"
Keywords: Diet therapy,Nutition,Dinh dưỡng học,Liệu pháp ăn kiêng